Poorly differentiated papillary thyroid carcinoma in a 5-year-old girl: a case report - Mohanned Mohsen; Omar Hamdy; Ahmad Ramadan; Shadi Awny; Khaled Zalata; Mohamed Ezat (SpringerOpen, 2024)
Abstract Background The incidence of thyroid cancer has been increasing among the population less than 20 years of age, especially during the second decade of life. Differentiated papillary thyroid cancer is the most common pathology in children. It usually presents with thyroid nodules with or without cervical lymphadenopathy. Thyroid nodules carry a considerable risk of malignancy in children. Case presentation We herein report a 5-year-old girl with poorly differentiated papillary thyroid cancer which is an extremely rare finding at this age. The patient underwent right thyroid lobectomy followed by left hemi thyroidectomy and right central and lateral neck dissection. Pathologic examination revealed a poorly differentiated papillary thyroid carcinoma with nodal deposits. Conclusion It is essential to raise awareness of proper evaluation and management of thyroid nodules at such an age.